Group 11 metal complexes of mesocyclic thioether-aminophosphonites, (-OC10H6) - Punji, Benudhar; Mague, Joel T.; Balakrishna, Maravanji S. (European Journal of Inorganic Chemistry, 2007)
Group 11 metal complexes of the mesocyclic thioether aminophosphonites [-OC10H6(μ-S)C10H6O-]PNC4H8E {2a: E = O; 2b: E = NMe; IUPAC names: 4-(dinaphtho[2,1-d:1′,2′-g][1,3,6,2]dioxathiaphosphocin-4-yl)morpholine (2a), 1-(dinaphtho[2,1-d:1′,2′-g][1,3,6,2]dioxathiaphosphocin-4-yl)-4-methylpiperazine (2b)} are reported. Thioether aminophosphonites 2a and 2b react with CuX (X = Cl, Br, and I) in a 1:1 molar ratio to give the tricoordinate, dimeric complexes [{[{-OC10H6(μ-S)C10H6O-}PNC4H8E-κP]Cu(μ-X)}2] (4a: E = O, X = Cl; 4b: E = NMe, X = Cl; 5a: E = O, X = Br; 5b: E = NMe, X = Br; 6a: E = O, X = I; 6b: E = NMe, X = I), whereas with 2:1 molar ratios monomeric complexes of the type[{[-OC10H6(μ-S)C10H6O-]PNC4H8O-κP}2CuX] (7a: E = O, X = Cl; 7b: E = NMe, X = Cl; 8a: E = O, X = Br; 8b: E = NMe, X = Br; 9a: E = O, X = I; 9b: E = NMe, X = I) are obtained in excellent yield. The P,S-chelated cationic complexes[{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP,κS}2Cu]BF4 (10a: E = O; 10b: E = NMe) are obtained when 2a and 2b are treated with half an equivalent of [(MeCN)4Cu]BF4. Similarly, thesilver complexes [{[{-OC10H6(μ-S)C10H6O-}PNC4H8E-κP,κS]AgCF3SO3}2] (11a: E = O: 11b: E = NMe) and [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP,κS}Ag(PPh3)]CF3SO3 (12a: E = O; 12b: E = NMe) are synthesized by the treatment of thioether aminophosphonites 2a and 2b with AgOTf and [Ag(PPh3)][OTf], respectively. Reactions of 2a and 2b with [AuCl(SMe2)] produce the simple monomeric gold(I) complexes [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP}AuCl] (13a: E = O; 13b: E = NMe). The iodo derivatives [{[-OC10H6(μ-S)C10H6O-]PNC4H8E-κP}AuI] (14a: E = O; 14b: E = NMe) are obtained by the halide-exchange reaction of 13a and 13b with CuI at room temperature. The structures of complexes 5a, 7a, 8a, 13a, 13b, and 14a are confirmed by single-crystal X-ray diffraction studies. In all of these complexes, the sulfur atom in the mesocyclic ring shows coordinative interaction towards the phosphorus atom, and in 5a, 7a, 8a, and 14a towards the metal center as well. (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2007)

General nickel-catalyzed method for C-H bond alkynylation of heteroarenes through chelation assistance - Punji, Benudhar; Khake, Shrikant manmathappa; Soni, Vineeta; Gonnade, Rajesh Ghanshyam (Chemistry - A European Journal, 2017)
A general nickel-catalyzed method for the alkynylation of heteroarenes through monodentate chelation assistance is described. Many heterocycles, including indoles, pyrroles, imidazoles and pyrazole, efficiently coupled with (triisopropylsilyl)alkynyl bromide, and synthetically important functional groups, such as halides, ether, nitrile, nitro were tolerated. Synthetic applicability of this Ni-catalyzed method is demonstrated by the removal of triisopropylsilyl (-SiiPr₃) group, and further functionalization into triazolyl, benzofuranyl and alkynyl arene derivatives. Preliminary mechanistic investigations on the alkynylation of indole suggest that the reaction proceeds through kinetically relevant C-H activation and follows the two-electron redox pathway. A catalytically competent Ni-species, [(Phen)₃Ni].NiBr₄ has been isolated and structurally characterized.